Biomonitoring for workplace exposure to copper and its compounds is currently not interpretable - Bevan, Ruth; Levy, Len (Elsevier, 2024)
This paper sets out to explore the requirements needed to recommend a useable and reliable biomonitoring system for occupational exposure to copper and its inorganic compounds. Whilst workplace environmental monitoring of copper is used to measure ambient air concentrations for comparison against occupational exposure limits, biological monitoring could provide complementary information about the internal dose of workers, taking into account intra-individual variability and exposure from all routes. For biomonitoring to be of reliable use for copper, a biomarker and the analytical ability to measure it with sufficient sensitivity must be identified and this is discussed in a range of matrices. In addition, there needs to be a clear understanding of the dose-response relationship of the biomarker with any health-effect (clinical or sub-clinical) or, between the level of external exposure (by any route) and the level of the copper biomarker in the biological matrix being sampled, together with a knowledge of the half-life in the body to determine accurate sampling times. For many biologically non-essential metals the requirements for reliable biomarkers can be met, however, for ‘essential’ metals such as copper that are under homeostatic control, the relationship between exposure (short- or long-term) and the level of any copper biomarker in the blood or urine is complex, which may limit the use and interpretation of measured levels. There are a number of types of biomarker guidance values currently in use which are discussed in this paper, but no values have yet been determined for copper (or its inorganic compounds) due to the complexity of its essential nature; the US The American Conference of Governmental Industrial Hygienists (ACGIH) has however indicated that it is considering the development of a biological exposure index for copper and its compounds. In light of this, we present a review of the reliability of current copper biomarkers and their potential use in the occupational context to evaluate whether there is value in carrying out human biomonitoring for copper exposure. Based on the available evidence we have concluded that the reliable use of biomonitoring of occupational exposure to copper and its application in risk assessment is not possible at the present time.
Keywords: Copper; Workplace; Biomonitoring; Feasibility; Guidance values